"We All Go Through It": Media Depictions of Mental Illness Disclosures From Star Athletes DeMar DeRozan and Kevin Love. (February 2021) - Parrott, Scott; Billings, Andrew C.; Buzzelli, Nicholas; Towery, Nathan
Mental illness remains stigmatized in the United States and abroad, with the mass media often blamed for perpetuating stereotypes about people who experience mental health issues. 2018 witnessed two professional basketball players—star athletes DeMar DeRozan and Kevin Love—disclosing personal experiences with depression and anxiety. Informed by social cognitive and framing theories, the present study examined how news stories characterized the disclosures, examining ways in which journalists presented the athletes as mental health advocates and models for pro-health attitudes and behavior. News stories generally framed the athletes as demonstrating character strength for disclosing mental illness in an athletic culture that often stigmatizes any potential weakness. Journalists often permitted the athletes to directly share their message concerning mental health with readers, as DeRozan and Love discussed (a) the experience of coming out; (b) the positive reception of teammates, coaches, and the public; and (c) the need for an end to mental health–oriented stigma. Stories often called for action, communicating to readers that people with mental illness are "not alone" and should share their experiences with others. The results provide the foundation for research into the relationship between media exposure and mental health-related attitudes, particularly how news framing of athletes' disclosures shape fan attitudes toward mental health treatment, mental illness, and people who experience mental illness.